PENDAMPINGAN DAN PELATIHAN GERAKAN PEMUDA ANSHOR SEBAGAI UPAYA MENINGKATKAN WAWASAN KEAGAAMAAN DAN NASIONALISME MASYARAKAT DESA PASINAN BOJONEGORO: ASSISTANCE AND TRAINING OF THE ANSHOR YOUTH MOVEMENT AS AN EFFORT TO IMPROVE RELIGIOUS INSIGHTS AND NATIONALISM OF THE COMMUNITY OF PASINAN BOJONEGORO VILLAGE - Fahrurrozi; Ida Fauziatun Nisa (Jurnal Pengabdian Masyarakat Kesosi, 2021)
Along with globalization and increasingly modern information, humans are faced with increasingly diverse problems. This also occurs in the rapidly growing growth and development of technology which always has a positive impact on society, not forgetting to also bring negative effects. As stated by Holger Borner in his remarks at the International Conference in Paris he said that globalization has actually become a fashion. However, the quality of speed in social relations is now finding new dimensions. Everyone who lives in society from the time he wakes up until he wakes up again or in other words the whole time, is naturally involved in communication. Communication occurs as a consequence of the existence of social relations (social relations) communication will occur when there are two or more people in society. Islamic religious education is guidance and care for students so that later after completing their education they can understand and practice the teachings of Islam and make it a way of life (way of life) everyday in personal and social life of society.